An analysis of the relationship between emotional intelligence and algebraic problem solving ability of secondary school students in Sokoto State, Nigeria - Julius, Elizabeth; Halim Abdullah, Abdul; Suhairom, Nornazira (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the relationship between emotional intelligence and the algebraic problem solving ability of secondary school students. 100 respondents were used as the sample for the survey at two secondary school in Sokoto state, Nigeria. The targeted respondents are senior secondary two (SSII) students in Sokoto state, Nigeria. Findings of the study showed that there is a moderate relationship between emotional intelligence of the students and their algebraic problem solving ability. Furthermore, it was discovered that male students have a low relationship in their emotional intelligence and their algebraic problem solving ability compared to the female students whose emotional intelligence and algebraic problem solving ability was found to be moderate.Â